Upbringing versus the Ethics of Responsibility - Kunicka, Małgorzata (INSTED: Interdisciplinary Studies in Education & Society, 2015)
The specific character of upbringing imposes the recognition of a human being, including their moral development, based not only on pedagogy, but also on philosophical sciences, amongst others on axiology and philosophical antropology. The process of upbringing always aims at raising such a personality of a pupil that allows them to make their own goals and values true taking into account a responsible action for the sake of common good. And it is the category of responsibility that has become the subject of reflection and consideration on various concepts of its phenomenon. The article presents three concepts of responsibility (by R. Ingarden, H. Jonas, E. Lévinas) creating ?a new wave? in the philosophy of responsibility and their threads possible to be used in the upbringing theory.